(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2024)
Ancient Indian cosmological concepts from the Vedic and Puranic eras reveal profound insights into the universe’s nature and origins. Swami Vivekananda emphasized the importance of understanding the past to shape the future, underscoring the need for a comprehensive analysis of Vedic literature. This survey explores various facets, including ancient Indian astronomy, the significance of celestial entities, and creation theories in key texts like the Vedas and Puranas. By examining these concepts, we can appreciate the interconnectedness of geography, mythology, and spirituality in ancient India.